2020
DOI: 10.1108/ijcthr-12-2019-0229
|View full text |Cite
|
Sign up to set email alerts
|

Life is better in flip flops. Digital nomads and their transformational travels to Thailand

Abstract: Purpose The metamorphosis within the Thai segment of the hospitality industry has influenced the global outlook for hospitality services, shifting the focus from leisure to a hybrid approach of providing all-inclusive work-leisure offerings. The purpose of this paper is, therefore, to outline the hybridisation of the hospitality industry in Thailand that is frequented by digital nomads, and to discuss the adaptation of local infrastructure to accommodate this trend. Design/methodology/approach Taking the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
(32 reference statements)
1
27
0
1
Order By: Relevance
“…This section summarizes ten main themes drawn in regards to coworking and coliving experience. The most recognized advantage is a community sense that includes easy access to meeting people and events; this finding is aligned with previous research [6][7][8][9][10]. In contrast to the community spirit, three participants indicated that they felt the lack of privacy at the same time:…”
Section: Findings and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This section summarizes ten main themes drawn in regards to coworking and coliving experience. The most recognized advantage is a community sense that includes easy access to meeting people and events; this finding is aligned with previous research [6][7][8][9][10]. In contrast to the community spirit, three participants indicated that they felt the lack of privacy at the same time:…”
Section: Findings and Discussionsupporting
confidence: 85%
“…Coworking and coliving space belong to the sharing economy, where the value is cocreated [4,5]. The majority of the previous studies recognized the value of bonding with like-minded individuals as the main advantage of coworking and coliving space [6][7][8][9][10]. Digital nomads tend to group within like-minded communities of locationindependent individuals [11].…”
Section: Overview Of Coworking and Colivingmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, contemporary coworking spaces, thoroughly flexible and towards collaboration orientated workspaces, have seen a significant increase in popularity amongst workers who sought engaging office grounds where they could ‘work along together’ (Spinuzzi 2012 ) while seeking social support (Gerdenitsch et al 2016 ) and collectivization (Avdiikos and Iliopoulou 2019 ) by actively or passively interacting with one another (Parrino 2015 ; Rus and Orel 2015 ; Grazian 2020 ). Due to the increasing demand, coworking spaces have soon started to appear both in urban and rural environments (Merkel 2015 ; Nakano 2020 ), seemingly transforming various micro-locations into centres for highly skilled and knowledgeable workers (Orel 2020 ; Grazian 2020 ; Mariotti et al 2021 ; Migliore et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A new segment of knowledge worker literature is developing around a new type of learner and worker of the 21 st century: the knowmad (Cobo & Moravec, 2011;Kubik, 2013;Moravec, 2008Moravec, , 2013aMoravec, , 2013bGarcia, 2012aGarcia, , 2012bOrel, 2020). The focus in the knowmad academic field is dedicated to the shifts in formal education and alternative competence development environments (e-learning).…”
Section: Introductionmentioning
confidence: 99%